Preparation of ZnO Microtube Capsule for Drug Delivery System via Microemulsion-Sol-Hydrothermal Method - Ji, Y.; Zhu, H.; Bao, H.H.; Zhang, L.; Yang, H.Z.; Zhang, X.D. (Asian Journal of Chemistry, 2013)
Cyclohexane, deionized water, CTAB and n-butyl alcohol were respectively adopted as oil phase, water phase, emulsifier and cosurfactant to prepare water-in-oil (w/o) emulsion. Zinc acetate dihydrate, monoethanolamine and ethanol was respectively adopted as reactor, complex agent and solvent to prepare the sol as the Zn source. Then the ZnO microtube capsule can be obtained through the hydrothermal route. X-ray diffraction and scanning electron microscope were chosen to investigate the crystallization properties and morphology of the sample. Results reveal that the hollow capsule with a few micrometers in size can be obtained through the combination of microemulsion-sol-hydrothermal method. Furthermore, a schematic model of the experiment is proposed.